Trends in the evolution of intronless genes in Poaceae - Yong Chen; Ting Ma; Tingting Zhang; Lei Ma (Frontiers in Plant Science, 2023)
Intronless genes (IGs), which are a feature of prokaryotes, are a fascinating group of genes that are also present in eukaryotes. In the current study, a comparison of Poaceae genomes revealed that the origin of IGs may have involved ancient intronic splicing, reverse transcription, and retrotranspositions. Additionally, IGs exhibit the typical features of rapid evolution, including recent duplications, variable copy numbers, low divergence between paralogs, and high non-synonymous to synonymous substitution ratios. By tracing IG families along the phylogenetic tree, we determined that the evolutionary dynamics of IGs differed among Poaceae subfamilies. IG families developed rapidly before the divergence of Pooideae and Oryzoideae and expanded slowly after the divergence. In contrast, they emerged gradually and consistently in the Chloridoideae and Panicoideae clades during evolution. Furthermore, IGs are expressed at low levels. Under relaxed selection pressure, retrotranspositions, intron loss, and gene duplications and conversions may promote the evolution of IGs. The comprehensive characterization of IGs is critical for in-depth studies on intron functions and evolution as well as for assessing the importance of introns in eukaryotes.